2021
DOI: 10.3389/fped.2021.583197
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT Scan for the Diagnosis of Pediatric Pulmonary TB: Radiological Findings and Its Diagnostic Significance

Abstract: Diagnosing active TB in children remains a clinical challenge, due to difficulties in achieving a definite microbiological confirmation, aspecific clinical manifestation, low sensitivity of chest radiography (CXR). For this reason, the use of chest computed tomography (CT) scan to evaluate suspected TB pediatric cases is increasing. We retrospectively reviewed records of patients aged <16 years diagnosed with active TB at the Pediatric Infectious Disease Unit of the Catholic University of the Sacred Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Previous studies reported the prevalence of lymph node calcification ranged from 9% to 28% (5,13,15,16). In the present study, only one (2%) patient with TB had lymph nodes with calcification, which appeared as specks.…”
Section: Discussionsupporting
confidence: 42%
See 4 more Smart Citations
“…Previous studies reported the prevalence of lymph node calcification ranged from 9% to 28% (5,13,15,16). In the present study, only one (2%) patient with TB had lymph nodes with calcification, which appeared as specks.…”
Section: Discussionsupporting
confidence: 42%
“…In our TB group, 22% of patients had isolated mediastinal LAPs without other associated parenchymal and/or pleural involvement. It was a significantly higher rate compared to the relevant literature (13,16). The presence of LAP without parenchymal involvement may be a good indicator for diagnosis of pulmonary TB in a relevant clinical setting.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations